Efforts to Increase Cadres Knowledge in Improving Fine Motorcy Development in Children Through Playdough Games : Upaya Peningkatan Pengetahuan Kader Dalam Meningkatkan Perkembangan Motorik Halus Pada Anak Melalui Permainan Playdough (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2023)
Fine motor development takes longer to achieve than gross motor development, so fine motor development is one aspect of children's development that needs to be stimulated, one of which is through playing techniques. The aim of health education is an effort to increase cadres' knowledge in improving fine motor development in children through playdough games. The method for implementing efforts to increase cadres' knowledge in improving fine motor development in children through playdough games is through lectures, demonstrations, questions and answers, pre and post tests. The results of the implementation of service activities went well and smoothly. Cadres and mothers who have toddlers or children are very enthusiastic about participating in activities. The results of the pre and post activity evaluation were that there was an increase in understanding of cadres and parents who have toddlers (children) in Wonotoro Village, District. Sukapura, Probolinggo Regency before and after the implementation of education.